Impaired Glucose Metabolism in Young Patients with First-episode Schizophrenia Aged from 16 to 35 Years - Yao, Jing; Chen, Nan; Xiu, Meihong; Wu, Fengchun; Huang, Yuanyuan (Current Neuropharmacology, 2025)
<span class=
Keywords: early stage of psychosis